E-waste management in selected institutions of higher learning in the Klang Valley, Malaysia / Pearson Kasapo - Kasapo, Pearson (2013)

(untitled)
“E-waste” is the term popularly used to refer to end-of-life or discarded electrical and electronic equipment. Institutions of higher learning (universities) contribute significantly to the rapidly growing threat of E-waste. This research seeks to establish if there are any institutional mechanisms for E-waste management and assess the level of university public (staff and student) knowledge on E-waste. The research focused mainly on Information and Communication Technology (ICT) E-waste management in selected universities in the Klang Valley of Central Region, Malaysia. ICT equipment (computers, printers, copiers) are the most widely used and frequently replaced electronics in universities and if not soundly managed pose grave environmental hazards because of their components which contain toxic substances such as lead, nickel, beryllium, mercury, cadmium, chromium, copper, lithium etc.